Vulnerabilidade ambiental à erosão do município de Teixeira de Freitas - BA - Almeida, Priscila Félix (2020)
The dimensions of the concept of Environmental Vulnerability are types of information that are crucial for planning the management of a given territory. The state of vulnerability of the environment should be considered decisive in the development of environmental planning instruments. This work aims to indicate the state of environmental vulnerability to erosion in the municipality of Teixeira de Freitas BA, whose territory suffered intense deforestation, followed by cattle ranching and a very high population increase, especially in the last seventy years. Thematic letters and other products used data available from several sources, such as IBGE, CPRM, Forest Forum of the Extreme South of Bahia and images from the Alos Palsar satellite. Digital processing was performed using ArcGIS software version 10.7 and QGIS version 2.18. The reference and coordinate systems adopted was the SIRGAS 2000 UTM 24S. The selected variables, generating the base maps were: Geology, Soils, Declivity and Land U se and Occupation. Vulnerability values were established for the various classes of these variables, which ranged from 1 (lowest vulnerability) to 5 (highest vulnerability), based on a methodological proposal developed and already replicated by other aut hors in regions close to the territory under analysis. The Environmental Vulnerability to erosion Map was the product of the overlapping of the base cards, with the sum of the values assigned to their respective classes, resulting in a vulnerability ladd er divided into five intervals: very low, low, medium, high and very high vulnerability. The geological and pedological classes present in the municipality showed values of low to medium vulnerability in most of its extension, since the geological cover is old, formed by stable lithological types and the soils are also old and well developed. The most determining factors for the highly vulnerable sections of the final map were the regions with high slopes and the most vulnerable forms of land use and occu pation. The remaining forest cover is very small and is in the initial or medium stage of restoration, with most of the municipality's territory occupied by pastures. After the generation of the final vulnerability map, refinement and grouping of isolated areas with up to 40, 100, 200, 500, 1,000 and 2,000 pixels was carried out, in order to make the map more operational from the point of view of territory management . However, the adoption of one or the other treatment depends a lot on the purpose of the u se. It is recommended for the elaboration of public policies at the municipal level the adoption of the treatment with grouping of areas of up to 200 pixels, which corresponds to the removal of isolated features with an extension of up to 3.13 ha, since in the other treatments there is serious and progressive decrease in areas of high vulnerability, which are priorities for public investments. It is hoped that this work can contribute to environmental planning in the municipality, and can also serve as a ba sis for the preparation of zoning